An Effective Approach to Achieve a Spin Gapless Semiconductor–Half‐Metal–Metal Transition in Zigzag Graphene Nanoribbons: Attaching A Floating Induced Dipole Field via π–π Interactions. (26th October 2012) - Guan, Jia; Chen, Wei; Li, Yafei; Yu, Guangtao; Shi, Zhiming; Huang, Xuri; Sun, Chiachung; Chen, Zhongfang
Abstract Under first‐principles computations, a simple strategy is identified to modulate the electronic and magnetic properties of zigzag graphene nanoribbons (zGNRs). This strategy takes advantage of the effect of the floating dipole field attached to zGNRs via π–π interactions. This dipole field is induced by the acceptor/donor functional groups, which decorate the ladder‐structure polydiacetylene derivatives with an excellent delocalized π‐conjugated backbone. By tuning the acceptor/donor groups, –C≡C– number, and zGNR width, greatly enriched electronic and magnetic properties, e.g., spin gapless semiconducting, half‐metallic, and metallic behaviors, with the antiferromagnetic−ferromagnetic conversion can be achieved in zGNRs with perfect, 57‐reconstructed, and partially hydrogenated edge patterns.